Analisis NPM, ROA, dan ROE dalam Mengukur Kinerja Keuangan - Slamet Heri Winarno (Jurnal Ekonomi, 2019)
This research aims to determine the financial performance of an expedition company based on company profitability analysis. Indicators of profitability used include the ratio of Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE) in 2016 to 2018. Assessment of company performance is done by comparing the rentability ratio with the average ratio Industry and Bank Indonesia standards. The data used are financial statement data that is balance sheet and income statement report for year 2014 until 2016. Result of research indicate that overall rentability performance show good value, but compared with industry average performance of NPM year 2014 show less result Good, while ROA and ROE performance during 2015 and 2016 has not shown satisfactory results because it is below the industry average. Overall financial performance of the company can be said good.